Aplicação de técnicas de redes neurais artificiais na previsão do nível do rio Tocantins na cidade de Tucuruí - CARNEIRO, Gean Kleber da Silva (2018)
The main source of energy in Brazil is the power of water. The Hydroelectrics do the work of transforming the driving force water into electrical energy. However, the planning of energy production in hydroelectrics is strongly dependent on the inflow and the amount of water in their reservoirs. In search of better planning, the electric companies are always concerned to improve their methods of control reservoir, that can, in addition to increase the productivity of the plant, meet the needs of the population living in the vicinity of the dam, with information that can be used in decision making, by local authorities, in the event of flood, which could impact the population at risk of overflow and to inundation, bringing injury or damage to residents living near the river.